2016
DOI: 10.1108/jsbed-05-2015-0058
|View full text |Cite
|
Sign up to set email alerts
|

“Opportunistic” spin-offs in the aftermath of an adverse corporate event

Abstract: Purpose -The purpose of this paper is to explore the inter-organisational dynamics, in terms of the triggers to spin-off formation and the genealogical inheritance of spin-offs, between a parent characterised by an adverse event and the spin-offs that emerge. The study focusses on the nature of the triggering event, exploring the heterogeneous nature of the processes by which some spin-offs are formed to exploit new opportunities created unexpectedly by an adverse event, and on the genealogical inheritance tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
(191 reference statements)
0
4
0
Order By: Relevance
“…These events or triggers can be understood as significant, positive or negative events that cause a change in the inertia of an individual's behavior (Shapero, 1975). Therefore, the study of such events is essential to understand the triggers that make an entrepreneur finally decide to or not to start a business project (Curran et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These events or triggers can be understood as significant, positive or negative events that cause a change in the inertia of an individual's behavior (Shapero, 1975). Therefore, the study of such events is essential to understand the triggers that make an entrepreneur finally decide to or not to start a business project (Curran et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Positive CSOs theories have been developed beyond motivations to include a multitude of market dimensions or pre-conditions to CSOs. Most notably, recent studies like Prezas and Simonyan (2015), Rocha et al (2015), Curran et al (2016) and Penela et al (2019) have built up the momentum of CSOs literature to consider external factors that affect CSOs decisions directly, motivate CSOs indirectly, or determining CSO outcome expectation. Prezas and Simonyan (2015) explores how the market valuation, performance, and degree of investor optimism or pessimism about the market at the time of divestitures affect the choice of managers between CSO and selloff decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that Pulled CSO does not outperform Pushed CSOs and Pushed CSOs recorded a higher survival rate comparatively. Curran et al (2016) explored new typologies of CSOs that are "opportunistic spin-offs," where they focused on studying Pushed CSOs' performance outcome, which was a reaction to an adverse event. We trail the arguments to the role of market optimism and circumstances of CSOs from these studies and focusing it on the outcome of the decision to achieve our goal of reporting market condition and performance tailorto-fit CSOs analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Academic spin-off topics included social capital (Borges & Fillion, 2013); causality and effectuation (Schleinkofer & Schmude, 2013); relational credibility (Bower, 2003) and growth (Doutriaux, 1987). Whereas, public funded spin-offs were analysed predominantly in light of the technology transfer process (Upstill & Symington, 2002), and corporate ventures via the influence of adverse conditions and inspiration (Curran et al, 2016;Thorén & Brown, 2010).…”
Section: Sociological Priority Grouping Focal Thematic Constituentsmentioning
confidence: 99%